Mitochondrial Phylogeny and Systematics of Palearctic Eagles - Ivan J. Starikov; Michael Wink (Пернатые хищники и их охрана)
The eagles sensu lato are a polyphyletic group of large raptors represented in the Palearctic realm by 13 species belonging to two subfamilies: Aquilinae (true Eagles) and Haliaeetinae (Sea Eagles). Phylogenetic position of this group taxa at species level and above based on nuclear and mitochondrial markers is currently clarified (Mindell et al., 2018), while intraspecific variability and genetic differences between subspecies are generally not well understood. This study examined the available mitochondrial DNA sequences from GenBank and BOLD databases, also unpublished sequences obtained by the authors were added.